PENGARUH UTILITARIAN VALUE, HEDONIC VALUE, DAN SYMBOLIC VALUE TERHADAP MINAT BELI (Studi Pada Live Streaming Shopee @Mayoutfitofficialshop) - Salsa Nurpadilah; Nenden Kostini; Cecep Safa’atul Barkah (POLITEKNIK LP3I JAKARTA, 2024)
In today's digital age, live streaming has become a dominant marketing platform, allowing for direct interaction between producers and consumers as well as providing a hands-on experience to users. Companies like Shopee @mayoutfitofficialshop have adopted live streaming as a key strategy to promote their products. This study identified the contribution of Utilitarian Value, Hedonic Value, and Symbolic Value in live streaming to consumer buying interest by involving 100 respondents in a quantitative and descriptive research design. Data from a questionnaire with a Likert scale of six answer choices were analyzed using descriptive statistics and multiple linear regression. The results show that Utilitarian Value, Hedonic Value, and Symbolic Value significantly influence consumers' buying interest in Shopee @mayoutfitofficialshop live streaming, emphasizing the important role of practical utility, fun, and symbolic value in the formation of buying interest on live streaming platforms such as Shopee @mayoutfitofficialshop.